The effects of hamstring cooling and crystretching on flexibility among healthy young adults - Mustafa Kamal, Ahmad Qamarul; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study utilizes a randomized crossover design to examine the acute effects of hamstring cooling and cryostretching on flexibility among twenty-five healthy young adults. Participants underwent three distinct conditions ice application alone, cryostretching (combining ice with proprioceptive neuromuscular facilitation), and a rest-only control with flexibility measured via pre- and post-intervention Sit-and-Reach Tests. By comparing these methods, the research evaluates the relative effectiveness of combined cryotherapy and stretching interventions to inform evidence-based practices for athletic performance and injury prevention.